HUBUNGAN ANTARA PERSEPSI KETERLIBATAN AYAH DALAM PENGASUHAN DENGAN KECERDASAN EMOSIONAL PADA SISWA LAKI-LAKI KELAS X SMK NEGERI 4 SEMARANG - SIANTI DEWI; Ika Febrian Kristiana (Faculty of Psychology, Diponegoro University, 2017)
Emotional intelligence plays an important role on someone’s attitude. The parents role most importantly on father figure is very important for his child moreover on the teenager age. The aim of this research is to understand the relation between perception of father’s involvement in parenting with the emotional intelligence of male students grade 10 SMK Negeri 4 Semarang. The subject of this research is male students grade 10 of SMK Negeri 4 Semarang. The number of sample used for this research is 211 pupils, with using a cluster random sampling technique. The data collectiong is using a Father Involvement Perception Scale (37 aitem valid; α = .93) and Emotional Intelligence Scale (40 aitem valid; α = .88) that has been tried out on 102 male students grade 10 of SMK Negeri 4 Semarang. Simple regretion analysis shows the positive and significance relation between father perception relation in parenting with the emotional intelligence, shown by the correlation coefficient rxy= .352 with p = .000. The higher father involvement perception on parenting, hence the higher the emotional intelligence of male students grade 10 SMK Negeri 4 Semarang, and vice versa. Father involvement perception in parenting give 12,4% of effective contributions to the emotional intelligence. This research is expected to be a consideration for students, parents, school, and also as a reference for further researcher.